Morphological Characteristics of the Lung during Lipopolysaccharide and Perfluorane Inhalation - A. M. Golubev; A. N. Kuzovlev; D. V. Sundukov; M. A. Golubev (Общая реаниматология, 2015)
The use of perfluorane for the cytoprotection of lung structures in gram-negative lung infections has been inadequately studied. Objective: to experimentally reveal the pattern of morphological changes in the lung during combined inhalation of lipopolysaccharide (LPS) and perfluorane that has cytoprotective properties. Materials and methods. The experiment was carried out on 35 outbred male albino rats weighing 320—350 g. The experimental animals were allocated to groups: 1) one-hour ventilation (controls) (n=5); 2) inhaled LPS 1.0 mg (n=10); 3) inhaled perfluorane 1.0 ml (n=10); 4) inhaled LPS 1.0 mg and then inhaled perfluorane 1.0 ml (n=10). Results. According to morphological findings, Group 1 (controls) was found to have no signs of lung structural changes. Group 2 (inhaled LPS) was noted to have signs of characteristic LPS-induced lung injury. Group 3 (inhaled perfluorane) showed complexes of macrophages with vacuolated cytoplasm (perfluorophages) in the bronchial lumen 3 hours after inhaled perfluorane administration. In Group 4, inhaled perfluorane exerted a cytoprotective effect: the degree of LPS- induced morphological changes in the lung was much lower than that in Group 2. Conclusion. The experimental model of LPS-induced lung injury indicated that LPS inhalation led to alveolar and bronchial epithelial damage, interstitial and alveolar edema, and obvious cell infiltration at the expense of lymphocytes, segmented leukocytes, and macrophages. This model showed that inhaled perfluorane reduced the signs of alveolar and bronchial epithelial damage and the degree of interstitial and alveolar edema. This supports clinical findings and offers possibilities of using inhaled perfluorane in resuscitation.